Testing choquet expected utility - Lukas Mangelsdorff; Martin Weber (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1992)
Many theories have been developed to model decision behavior under ambiguity. In this paper we empirically investigate theories which are based on non-additive probabilities, i.e. Choquet expected utility (CEU) theories. We first replicated Ellsberg-paradox behavior. Then we elicited the individual non-additive probabilities, the so called capacities. Those capacities did not have all properties theoretically required. Finally we found that CEU is not really superior to EU in predicting the participants' decisions. – – Betrachtet werden Entscheidungen unter Ambiguität, d.h. Entscheidungen unter Unsicherheit über Wahrscheinlichkeiten. Wir untersuchen empirisch die Theorien, die Entscheidungsverhalten bei Ambiguität durch nicht-additive Wahrscheinlichkeiten abbilden (Choquet-Erwartungsnutzentheorie). Zunächst replizieren wir sogenanntes Ellsberg-paradoxes Verhalten. Die sich aus der Theorie für die Ermittlung der nicht-additiven Wahrscheinlichkeiten, der Kapazitäten, ergebenden Implikationen werden nur teilweise bestätigt. Abschließend wird gezeigt, daß die Choquet-Erwartungsnutzentheorie das Entscheidungsverhalten der Experimentteilnehmer nicht besser als die Erwartungsnutzentheorie vorhersagt.
Keywords: 650; Ellsberg paradox; ambiguity; Choquet expected utility; non-additive probabilities; experimental economics